A morphological study of Aristolochia holostylis (Aristolochiaceae) reveals the presence of a new species - Frank, Dominik; Lombardi, Julio A. [UNESP]; Monro, Alexandre K. (Springer Nature, 2022)
Aristolochia holostylis has long been construed as constituting a single widespread and variable species, ranging across Paraguay, Bolivia, and Brazil. However, our morphological analysis shows that populations in Bolivia, Paraguay and western Brazil differ by several constant characters of the perianth and indumentum from those in northeastern Brazil. The type specimen possesses the typical morphology of the latter populations; thus, they retain the name A. holostylis, whereas the former populations are recognized here as belonging to a new species, A. pyriflora. We provide new descriptions for both species, along with morphological comparison between them, illustration of diagnostic characters and geographic distributions, and assessment of their respective conservation statuses. The often overlooked infraspecific name Holostylis reniformis f. minor is placed in the synonymy of A. pyriflora.
Keywords: Flora of Brazil; Holostylis; new species; taxonomy